(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2019)
The films of polymeric composites containing monomers of azobenzene dyes or azobenzene lateral groups chemically bonded to the main polymer chain demonstrate photoactive properties, and can be used in electrooptical light modulators and in recording media (RM) for polarization holography. Photoinduced optical anisotropy (PIA) appears under influence of linearly polarized light caused by the processes of trans-cis-izomerization of the azobenzene groups. This process is determining for application of the considered materials as RM for polarization holography. The films of polymeric polarization sensitive media based on a copolymer of styrene with nonyl methacrylate doped with azobenzene-type dyes with different electron-acceptor substituents are obtained in this work. In the films of copolymer the holograms of the plane wave front were registered for parallel and orthogonal orientations of polarization vectors of the object and reference light beams. Their photoelectrophysical, in particular photodielectric, and information properties are investigated. It was established, that when the mutual orientation of the recording beams changes from the orthogonal to parallel orientation the diffraction efficiency of the holograms increases in the case of using azo dye with the maximum number of auxochromic substituents in the molecule. The effect of the diffraction efficiency dependence on the chromophores structure is connected with the deepening of dye color. The photo-induced optical anisotropy in the films appears due to a change of the concentration ratio of trans- and cis-isomers of azobenzene dye fragments. This conclusion is confirmed by the photodielectric measurements data, namely, by the negative sign of the photodielectric effect, observed experimentally in the investigated thin film structures. It was shown, that investigated compositions can be used as information media for polarization holography.